Acceptability and Reliability of the Bayley Scales of Infant and Toddler Development-III Among Children in Bhaktapur, Nepal - Ranjitkar, Suman; Kvestad, Ingrid; Strand, Tor A.; Ulak, Manjeswori; Shrestha, Merina; Chandyo, Ram K.; Shrestha, Laxman; Hysing, Mari (Frontiers in Psychology, 2018)
Background The Bayley Scales of Infant and Toddler Development (Bayley-III) is the most widely used developmental assessment tool worldwide, but less is known about its psychometric properties and feasibility in a setting of low and middle income countries. Aim To assess the psychometric properties and feasibility of the Bayley–III when used in a large scale randomized controlled intervention trial in Nepal. Method The participating infants were part of a randomized, doubled blind, placebo controlled trial to measure the efficacy of vitamin B12 supplementation on growth and neurodevelopment. 600 children aged 6-11 months were enrolled and included for developmental assessment. The Bayley–III measures child development across five domains: cognition, receptive and expressive language, fine and gross motor. Some items of the subtests were culturally adapted. To measure and ensure appropriate inter-observer agreement, standardization exercises were performed during the initial training, and double scoring of seven % of test sessions were conducted throughout the study by two examiners. Results The inter-rater agreement was excellent for both the standardization before the start of the study, and for the quality control throughout the study with ICC ranging from 0.95 to 0.99. The internal consistency measured by the Cronbach’s alpha coefficient ranged between 0.57 to 0.87. The subtests with raw scores as well as scaled scores were significantly correlated (p<0.001). The means and standard deviations of the scaled scores compared with American norms were similar to the distribution in the American sample, with the exception of the receptive (Mean=7.67, SD=2.167) and expressive (Mean=7.29, SD=1.904) language subtests that were lower than the American norms. Conclusion The inter-rater reliability was excellent between the scorers on the Bayley-III both during standardization and for the quality control. The distributions for the cognitive and motor subscales are comparable to the American norms, while caution is needed in the interpretation of the language scales. The results suggest that Bayley-III is a feasible and reliable tool for the assessment of neurodevelopment status in nutritional studies in low resource settings such as Nepal. Cultural adaptations, training and standardization are prerequisite for a valid and reliable assessment using the Bayley.